Modeling analysis of automatic parking path planning for wheeled AGV. Issue 1 (1st July 2022) - Zhao, Y J; Ma, S W; Cheng, Y
Abstract: Path planning is an important part of vehicle automatic parking. In this paper, the vehicle kinematics model is built based on the Ackerman steering principle, and the automatic parking path planning is explored. The starting conditions of one-step vertical parking are determined, the kinematic constraints are summarized, the parking tracking scheme is designed, and the parking path planning model is established. The parking path is fitted by B-spline curve to obtain the path optimization function. The parking space coordinate system is established according to the vertical parking space, and the parking path data obtained by simulation are input into the vehicle controller for one-step vertical parking test. The test results show that the error between the real vehicle test parking trajectory and the set trajectory is within the allowable range by using the parking path planning algorithm, indicating that the parking path planning strategy is effective.